Protein and lipid content of microalgae scenedesmus sp. biomass grown in wet market wastewater - Mohd Apandi, Najeeha; Radin Mohamed, Radin Maya Saphira; Ahmad Latiffi, Nur Atikah; Mohd Rozlan, Nur Farahanim; Abduh Algheethi, Adel Ali Saeed (EDP Sciences, 2017)
Microalgae biomass is a type of organism that has various advantages and often used for variety of uses not only for wastewater treatment purposes but also serve as bio-based products development. Because of high in protein and lipid accumulation, this freshwater microalgae Scenedesmus sp. was selected for the present study. In this study, microalgae Scenedesmus sp. was grown in four concentrations of wet market wastewater (10%WM, 15%WM, 20%WM and 25%WM) in comparison with the Bold Basal Medium (BBM) as a control. The result shows that the highest protein content (50.72%) was in 10%WM followed by 15%WM, 20%WM, 25%WM and BBM. As for lipid content, the best concentration was obtained in the 25%WM with the value of 26.7% compared to other concentrations and BBM. Therefore, the result indicates that microalgae Scenedesmus sp. biomass cultured using wet market wastewater has a great potential in producing protein-rich and lipid content which significantly could be used as a fish feed product.